Розробка компонентів інформаційної системи для пошуку та співпраці DevOps-фрілансерів і роботодавців - Чернишова, П. О. (ХНУРЕ, 2025)
This work is devoted to the development of a web platform for interaction between DevOps freelancers and employers, which provides effective candidate search and resume improvement using artificial intelligence. The built-in AI analyzes and optimizes freelancers` resumes, providing recommendations for ІТs improvement. The research focuses on the development of key components of the platform, in particular, an information system for storing and processing data, a rating mechanism, as well as functionalІТy for publishing projects and vacancies.
Keywords: DevOps фріланс; роботодавець